IDENTIFICATION OF COPPER-INDUCIBLE GENES IN SWORDTAIL FISH (Xiphophorus spp.) USING DIFFERENTIAL DISPLAY - Dwinna Aliza; Tengku Muhammad (Universitas Syiah Kuala, 2008)
Differential display technique was used to identify differentially expressed gene ofswordtail fish (Xiphophorus spp.) that induced by 1 µg/ml copper for 24 hours. From eightprimers that have been used for differential display, seven of them showed the differentialgenes which were not present in the control. The reamplification of these fragments rangingfrom below 100 to 200 bp. But only two fragments were successfully cloned and sequenced,those are H-AP10 and H-AP11. Sequence analysis showed that both of the sequences revealedhigh similarity with Homo sapiens stress-associated endoplasmic reticulum protein, a signalgenerated that induces apoptosis.Keywords: differential display, swordtail fish, copper pollution, mRNA expression, biomarker